Kajian Pengaruh Penggunaan Zat Admixture ” X”, Fiber Dan Semen Grouting Terhadap Kuat Tekan Dan Retak Beton Pada Beton Tanpa Perawatan - Aland Surya Nugroho; Theovilla Arry (Universitas Katolik Soegijapranata Semarang, 2019)
At present, there are many damages to concrete structures in buildings that have build. One such damage is the appearance of cracks. Cracks in concrete are caused by many factors, including loads that exceed limits, temperature, components of the constituent material, the process of making concrete and time.This research was conducted with the aim of studying the effect of the use of admixture